Does Alexithymia Affect Memory for a Crime? The Relationship Between Alexithymia, Executive Functions, and Memories - Battista, Fabiana; Lanciano, Tiziana; Curci, Antonietta (Frontiers in Psychology, 2021)
Prior studies on alexithymia and memory have found a negative association between the two constructs, especially when emotional memories are considered. Moreover, it has been demonstrated that also individuals’ executive functioning (EF) influences this relationship. Thus, the goal of the present study is to verify whether alexithymia can influence the memory accuracy for a violent crime in people with different levels of EF resources both in terms of correct details and memory distortions (i.e., omissions and commissions) reported. We assessed individuals’ alexithymia and EF resources and showed participants a video of a violent crime (i.e., murder). We then asked participants to testify about the content of the video by imagining to be witnesses of the crime. A memory test was run on two moments in time: Immediately after the video presentation and after ten days. Findings demonstrated that alexithymia influences the recall of the event both in participants’ proneness to report correct details and memory distortions (i.e., omissions and commissions). Additionally, we found a contribution of EF resources in this relationship. Our findings provide new information for legal professionals on memory functioning.